Experimental Study on the Production and Mechanical Behavior of Compressed Lime-Cement-Stabilized Interlock Soil Blocks - Besukal Befikadu Zewudie (Advances in Materials Science and Engineering)
Compressed stabilized soil block is a sustainable building material primarily made up of stabilized damp soil compressed under pressure. Soil properties and the type of the stabilizer used in producing compressed soil blocks have a significant impact on the quality and behavior of the soil blocks. This study presents the physical and mechanical behavior of lime-cement-stabilized compressed interlock soil blocks produced from two types of natural soil. The two types of soil have different index properties and mineral oxide compositions. Lime-cement combination and cement standalone was used as a binder in the production of test sample blocks depending on the index properties of the soil. 2%lime + 6%cement, 3%lime + 8%cement, and 4%lime + 10%cement were used for the soil block produced from silty clay soil of medium plasticity index. On the other hand, 6%, 8%, and 10% cement by dry mass of soil were used to stabilize silty sand soil. The behaviors of the blocks, such as dry density, the initial rate of water absorption, saturated absorption of water, compressive strength, and stress-strain relation, were examined. The result shows that the compressed soil blocks produced from lime-cement-stabilized silty clay soil has a low rate of initial water absorption and a low dry unit weight when compared to cement-stabilized sandy soil blocks. Soil blocks produced from cement-stabilized silty sand soil attain greater compressive strength by more than 50% of the compressive strength of silty clay soil blocks stabilized by a combination of lime and cement at 60 days after production. The initial tangent modulus of the soil blocks produced using a manual compressing machine from a clay soil stabilized by the lime-cement proportions of 2%L + 6%C, 3%L + 8%C, and 4%L + 10%C is about 1,700 MPa–2,300 MPa with a dry density greater than 1,660 kg/m3.